Produção do cuidado na estratégia saúde da família em um cenário da Bahia: acesso, vínculo e responsabilização? - Amorim, Anne Caroline Coelho Leal Arias (2010)
This paper discusses the practice of health staff at the Family Health Strategy (FHS), which occurs through access to services, transversalized by the possibility of development of the link-responsibility in Bahia, Brazil in 2009. This is a qualitative research, with the techniques of data collection: semi-structured interviews and systematic observation. The flowchart analyzer guided the data analysis. The study subjects were 29 people: group I (health workers-18): group II (users-9), group III (managers - 2). Results showed that access occurs preferentially through the arrival order, the family registration and programs aimed at specific groups. The initial contact in the "Family Health" is held at reception, a privileged space for the use ofsoft technology, being manifested in a tense and conflicting way, but with the potential to construct new ways to welcome the user. The practice procedure guides focused attention on the FHS, emphasizing also the emergency room, pictured in emergency/ urgency care. The therapeutic process varies: clinical appointment, emergency care, scheduled returns, health education, home visits, team meetings and with the community or by referral to other network services. However, the health teams perform various forms of "attention" at the entrance, being dependent on the commitment and subjectivity of that work in practice and the development or not of the link responsibility in the (co) production of care. The network of relations established in practice for health care manifests itself from different carer acts of subjects intertwined in practice (management, workers and users), according to the uniqueness and commitment of everyone who works in the strategy, which depending on the intent, express several degrees of link- responsibility. However, some activities performed by nurses were more susceptible to new therapeutic attitudes, expressed by the users' satisfaction. The study highlights the need to advance in the (re) signification of practices to enhance the improvement of access at "gateway" system.